Roland reflects on the implications of generative artificial intelligence on homo-digitalis - Bruin, Dieter de (HTS teologiese studies, 2025)
The rapid development of artificial intelligence (AI) has sparked theological debates about its potential to achieve consciousness and personhood. This article critically evaluates these claims, arguing that consciousness cannot emerge from computational systems as an intrinsic quality of living beings. Through philosophical analysis and theological reflection, it examines the fallacies in attributing agency or personhood to AI.Contribution: These reflections are offered in a playful reflective tone, drawing on the form and content from two creative works by David Bentley Hart, where persons other than human beings are given voice to critique an algorithmic and mechanistic development of consciousness.